Antioxidant activities of Hypochaeris laevigata var. hipponensis: Endemic species from Algeria - Nabila SOUILAH (International Journal of Sciences and Natural Ressources, 2022)
Hypochaeris laevigata var. hipponensis (Asteraceae) is an endemic plant from Algeria. In the current study, we analyzed for the first time the antioxidant activities by five methods (β-Carotene bleaching test, DPPH test, ABTS radical cation reduction test, CUPRAC test, Ferrous ions chelating test) of three fractions of aerial part of plant: dichloromethane (DCM), ethyl acetate (EA) and n-butanol (BuOH). We also determined the total phenolic and flavonoid contents. The fraction EA showed the highest values, followed by BuOH and DCM fractions. Furthermore, the antioxidant action was dictated by five methods and the tested plant fractions demonstrated a noteworthy antioxidant action.